2011
DOI: 10.1002/polb.22244
|View full text |Cite
|
Sign up to set email alerts
|

The role of alkane dithiols in controlling polymer crystallization in small band gap polymer:Fullerene solar cells

Abstract: The effect of the addition of 1,8‐octanedithiol (ODT) during processing on the microstructure of blend films of poly[2,6‐(4,4‐bis‐(2‐ethylhexyl)‐4H‐cyclopenta[2,1‐b;3,4‐b′]dithiophene)‐alt‐4,7(2,1,3‐benzothiadiazole)] (PCPDTBT) and [6,6]‐phenyl‐C71 butyric acid methyl ester ([70]PCBM) is studied. Grazing incidence X‐ray diffraction and absorption spectroscopy show that the crystalline order of PCPDTBT increases when ODT is introduced in the solution phase either to neat polymer systems or to blends with [70]PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
105
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 43 publications
14
105
1
Order By: Relevance
“…Subsequently, it was noticed that PCPDTBT crystallized under the influence of the additive. 94,95 GIXD showed the ordered packing of PCPDTBT chains and the chain packing assumed an edge-on orientation, similar to that seen in thin films of P3HT [ Fig. 15(e)].…”
Section: Polyfluorene-based Polymermentioning
confidence: 76%
“…Subsequently, it was noticed that PCPDTBT crystallized under the influence of the additive. 94,95 GIXD showed the ordered packing of PCPDTBT chains and the chain packing assumed an edge-on orientation, similar to that seen in thin films of P3HT [ Fig. 15(e)].…”
Section: Polyfluorene-based Polymermentioning
confidence: 76%
“…[ 18 ] It was proposed that the increase in electron mobility on annealing is due to the aggregation of P3HT, driving phase separation and the formation of a connected and more ordered PCBM phase. [ 4,19,20,[35][36][37][38][39][40] Those studies concluded that electron collection limits the performance of the PCPDTBT:PCBM blend, but that the performance of the blend could be enhanced through use of ODT or DIO solvent additives, or by substituting the polymer with a silicon-bridged analogue. [ 34 ] The adverse effect on electron mobility of blending polymer and fullerene has also been demonstrated for PCPDTBT:PCBM in a number of studies.…”
Section: Electron Transport As a Limiting Factor In Ptb7:pcbm Blendsmentioning
confidence: 99%
“…However, a more recent paper by Agostinelli et al reported a β of 4 × 10 − 12 cm 3 s − 1 for the C-PCPDTBT:PC 70 BM blend. [ 14 ] Furthermore, Peet et al [ 7 ] have shown that the fi ll factor of Si-PCPDTBT:PCBM blend devices drops rapidly with increasing active layer thickness (from > 60% at 100 nm to < 45% at 200 nm). This result is inconsistent with Si-PCPDTBT being a nonLangevin system.…”
mentioning
confidence: 98%